Penerapan Seni Melipat Kertas dalam Meningkatkan Motorik Halus Anak Kelompok B di RA Hidayatus Shibyan Tiris Probolinggo - Kasihhatin (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to describe the process of implementing paper folding art (origami) and its impact on the development of fine motor skills in Group B children at RA Hidayatus Shibyan Tiris Probolinggo. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation, and subsequently analyzed using the Miles and Huberman model. The findings indicate that the application of origami is carried out through an integrated process of planning, implementation, and evaluation, incorporating religious values and local cultural elements. This activity enhances finger muscle strength, eye-hand coordination, movement precision, focus, patience, and children's self-confidence. The integration of Islamic values is realized through the selection of meaningful folding shapes, religious storytelling, and social practices such as mutual assistance. The study's findings underscore that origami is an effective medium for stimulating fine motor skills while simultaneously serving as a tool for character building in early childhood. This research contributes to the development of a contextual, religious, and holistic arts-based early childhood education model, providing valuable insights for educators and policymakers